CONTEMPORARY WAQF AND FAMILY IN MUSLIM COUNTRIES: LEGAL REVIEW IN TAHIR MAHMOOD’S PERSPECTIVE - Ferida Rahmawati; Hendri Hermawan Adinugraha (Journal of Islamic Studies and Humanities, 2022)
The purpose of this study is to describe contemporary waqf and family law in Muslim countries in the perspective of tahir mahmood. This research method uses a literature review approach whose main source is a book by Tahir Mahmood, entitled “Family Law Reform in the Muslim World”, published by N.M. Tripathi PVP, Ltd., Bombay, in 1972, with a total of 336 pages. This literature review concludes that broadly speaking, the legal system in force in Muslim countries consists of three parts, namely: a system that still applies sharia as human law (principal) and seeks to apply it in all aspects of human relations as a whole, abandon sharia and replace it with a completely secular law, and a system that tries to take a moderate path between the two extreme legal systems, namely implementing Islamic law in full and a system that completely rejects Islamic law. Based on the three patterns of application of Islamic law in Muslim countries, it shows that the differences in the system and form of renewal of Islamic law are not only caused by the political system adopted, but also by the historical, sociological and cultural differences of each Muslim country. The ijtihad mechanism in positivizing legislation of waqf and social problems has been carried out by sharia law reformers to answer some contemporary legal issues through the use of takhayyur and talfiq.